ANALISIS PENGEMBANGAN USAHA ROTI KUKUS PANGGANG (STUDI KASUS PADA KEDAI BI’LIS BAJENG PERMAI) - Nurjannah; Nurdiana, Nurdiana; Ulfa Damayanti, Ulfa Damayanti3 (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the business development of Kedai Bi'lis Bajeng Permai in innovating on development to be able to compete and survive in running the steamed toast business. This study uses a qualitative method, where the data obtained comes from interviews with several informants and through questionnaires filled out online via Google Form. The results of the study are (1) the need for creativity in developing a business with the development of ideas for the products produced such as the number of menus, appearances or unique product forms so as to attract the attention of consumers; (2) the need for innovation towards more creative baked steamed bun products; (3) the development of the steamed toast business can be done with creativity and innovation as well as implementing online marketing or sales strategies.